Role of FNAC in the diagnosis of cysticercosis - Parakh, Richa; Gupta, Sumit; Singh, Swati; Garewal, Jaydeep; Rajput, Rashmi; Vashist, Shelly (International Journal of Medical Research and Review, 2016)
Background and Objectives: Cysticercosis is a common tropical disease. Human cysticercosis is caused by the dissemination of the embryo of Taenia solium in the intestine via the hepatoportal system to the tissues and organs of the body. The organs most commonly affected are the subcutaneous tissues, skeletal muscles, lungs, brain, eyes, liver, and occasionally the heart, thyroid, and pancreas. Fine needle aspiration cytology (FNAC) plays an important role in prompt recognition of this disease. Aims: To study the role of FNAC in the diagnosis of cysticercosis. Methods: Fifteen patients with subcutaneous and intramuscular nodules, who were clinically diagnosed as lipoma, neurofibroma, lymphadenitis, cold abscess, epidermal inclusion cyst, sebaceous cyst, fibroadenoma and cysticercosis were included in the present study. Results: In 4 (26.6%) cases, a definitive diagnosis of cysticercosis was obtained in the form of fragments of parasite bladder wall and, biopsy confirmed the diagnosis. In the rest 11 (73.3%) cases, larval fragments could not be identified on the aspirates and the diagnosis of parasitic inflammation was suggested on the basis of other cytomorphological findings. Follow-up biopsy confirmed the diagnosis of cysticercosis. Conclusions: Cysticercosis is continuing to be a major health problem in developing countries. Fine needle aspiration cytology (FNAC) is cost effective and simple procedure. The cytological diagnosis is quite straightforward in cases where the actual parasite structure is identified in the smears. However, in other cases, presence of eosinophils, histiocytes, a typical granular dirty background are the features which should always alert the pathologist to this possibility.